The Effect of NSAID Pretreatment on Aqueous Humor Prostaglandin E2 Concentration in Eyes Undergoing Femtosecond Laser-Assisted Capsulotomy - Vasilios F. Diakonis; Apostolos G. Anagnostopoulos; Angeliki Moutsiopoulou; Nilufer Yesilirmak; Florence Cabot; Daniel P. Waren; Terrence P. O’Brien; Sonia H. Yoo; Robert J. Weinstock; Kendall E. Donaldson (Journal of Ophthalmology)
Purpose. To assess aqueous humor concentration of prostaglandin E2 (PGE2) after capsulotomy creation using a femtosecond laser (FLAC) in patients pretreated with short-term topical ketorolac versus patients without pretreatment. Methods. This prospective study comprised consecutive patients scheduled to undergo cataract surgery using a femtosecond laser platform to perform only capsulotomies. An identical protocol for preoperative mydriasis was used for all the eyes included in the study, while aqueous humor was extracted from the anterior chamber of all patients immediately after the initial side port incision. ELISA was performed to quantify aqueous humor PGE2. The patients were divided into 2 groups; in group 1, the patients received short-term topical ketorolac preoperatively, while the patients in group 2 did not receive NSAID pretreatment. Results. Twenty eyes of 20 patients were included in the study (10 eyes in each group). Mean concentration of aqueous humor PGE2 after FLAC was 392.16 ± 162.00 pg/ml and 622.63 ± 331.84 pg/ml for groups 1 and 2, respectively. A statistically significant difference in aqueous humor PGE2 concentration between the two groups (p<0.05) was demonstrated, with the eyes that received ketorolac pretreatment demonstrating a lower concentration of PGE2. Conclusion. Short-term topical use of ketorolac prior to FLAC seems to prevent excessive release of PGE2 in the anterior chamber of the eyes that received NSAID pretreatment when compared to the eyes that did not receive NSAIDs preoperatively.